The transatlantic trade and investment partnership: Negotiations status quo and the relevance for the Romanian public debate - Oana-Antonia Colibăşanu; Victor-Vlad Grigorescu; Eliza Vaş (European Institute of Romania, 2015)
The Transatlantic Trade and Investment Partnership negotiations are important not only for the business environment, but also for the society in general, considering that it aims at establishing a new set of rules for trade and investment between the two largest partners in the global economy. Considering the growing regional importance of Romania, but also the socio-economic challenges that the EU is currently facing, we have aimed at providing a framework for understanding the status quo of the TTIP negotiations, as well as their general implications for the EU integration processes in what regards trade and investment and, more generally, the common market. We have also looked at Romanian public debate and, taking into consideration the available data, we have analysed the main concerns stemming from the current discourse. We concluded by outlining some of the main questions that Romania has to tackle before establishing policies in order to make the most of the current TTIP negotiations. The proposed Working Paper does not seek to provide recommendation on policies, but instead to summarize the main concerns for the future in what regards TTIP, in general, and Romania's risks and benefits considering current negotiations, in particular.
Keywords: 330; TTIP; transatlantic negotiations; European integration; ISDS